2016
DOI: 10.1002/ana.24571
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Depletion in Respiratory Chain–Deficient Parkinson Disease Neurons

Abstract: ObjectiveTo determine the extent of respiratory chain abnormalities and investigate the contribution of mtDNA to the loss of respiratory chain complexes (CI–IV) in the substantia nigra (SN) of idiopathic Parkinson disease (IPD) patients at the single‐neuron level.MethodsMultiple‐label immunofluorescence was applied to postmortem sections of 10 IPD patients and 10 controls to quantify the abundance of CI–IV subunits (NDUFB8 or NDUFA13, SDHA, UQCRC2, and COXI) and mitochondrial transcription factors (TFAM and TF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
162
8
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 207 publications
(200 citation statements)
references
References 41 publications
10
162
8
2
Order By: Relevance
“…Our findings do not corroborate the current hypothesis that complex I deficiency in PD may be the result of accumulating deletions and quantitative depletion of the mtDNA [4,16]. Moreover, ultra-deep-sequencing studies in single neurons and brain homogenates have shown no difference in the point mutational burden of mtDNAencoded complex I genes between PD individuals and controls, suggesting that mtDNA point mutations do not contribute to the observed complex I deficiency [8,13].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings do not corroborate the current hypothesis that complex I deficiency in PD may be the result of accumulating deletions and quantitative depletion of the mtDNA [4,16]. Moreover, ultra-deep-sequencing studies in single neurons and brain homogenates have shown no difference in the point mutational burden of mtDNAencoded complex I genes between PD individuals and controls, suggesting that mtDNA point mutations do not contribute to the observed complex I deficiency [8,13].…”
Section: Discussioncontrasting
confidence: 99%
“…Serial 3 μm thick sections were stained with primary antibodies (all from Abcam) against complex I (NDUFB8, ab110242, dilution 1:300), complex II (anti-SDHA, ab14715, dilution 1:4000), complex III (anti-UQCRC2, ab14745, dilution 1:10,000), complex IV (COX-I, ab14705, dilution 1:10,000), complex V (ATP-synthase, ab14748, dilution 1:10,000), and the mitochondrial membrane marker porin (VDAC1, ab14734, dilution 1:10,000). We chose the NDUFB8 subunit because it is central to complex I assembly and function [10,39,46] and has been widely used as a marker of the integrity of the complex [16,40,41]. Sections were deparaffinised in Histoclear and rehydrated in graded ethanol.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Mitochondria are complex organelles that not only participate in ATP synthesis and ROS production, but also play important roles in proliferation, differentiation, and apoptosis of germ cells [17,18]. Mitochondrial function depends not only on mitochondrial molecules encoded by nuclear DNA (nDNA), but also depends on molecules encoded by mitochondria DNA (mtDNA) [19,20]. The literature shows that many kinds of abnormal expression of mitochondrial proteins are associated with mitochondrial dysfunction, resulting in mitochondrial diseases such as neurodegeneration, cancer, infertility, and ageing [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…It accumulates throughout life and is thought to contribute to diseases of aging that include neurodegeneration, metabolic disorders, cancer, heart disease, and sarcopenia [126,127]. A new investigation of mtDNA in the dopaminergic neurons [128] expanded the previous results showing a prevalent deletion in single neurons on a background of multiple mtDNA deletions [129]. It showed that complex I and complex II are most consistently affected in single neurons, which also displayed a reduced mtDNA copy number [128].…”
Section: Drosophila Melanogaster -Model For Recent Advances In Genetimentioning
confidence: 92%